The Influence of Corporate Governance on Enterprise Risk Management: A Systematic Literature Review - Citra Triasma; Isnuhardi Isnuhardi (BUGIS : Journal of Business, Technology, & Social Science, 2026)
This study analyzes the influence of corporate governance on enterprise risk management (ERM) through a Systematic Literature Review (SLR) of 22 international journal articles published between 2017 and 2026. The results show that corporate governance generally has a positive impact on ERM (86% of the reviewed articles). Mechanisms such as board independence, directors’ financial expertise, risk committees, and audit committees are proven to enhance ERM effectiveness. Agency Theory emerges as the most dominant theoretical framework (41%). A small number of studies report weaknesses in implementation, limitations in ERM integration, and conservative tendencies associated with gender diversity. This study concludes that corporate governance is a crucial foundation for effective ERM; however, its success depends on the context and the design of governance mechanisms.